Performance of US and European exchange traded funds: A base point-slack-based measure approach - Carla Oliveira Henriques; Elisabete Duarte Neves; Jeremias A. Conceiç\~ao; Elisabete F. Sim\~oes Vieira (Journal of Risk and Financial Management, 2023)
This study evaluates the performance of United States (US) and European Exchange Traded Funds (ETFs) using the non-oriented version of the base point-slack-based measure (BP-SBM) Data Envelopment Analysis (DEA) model, which allows for handling negative data that can arise in some of the metrics traditionally used in this type of analysis. Our findings show that US efficient ETFs are considered benchmarks more often than European efficient ETFs. Nonetheless, it was possible to conclude that European inefficient ETFs were generally less inefficient than US ETFs. Our findings also show that ETFs' efficiency (particularly for US ETFs) in the short run is more related to risk than to profitability factors. This implies that as the time horizon lengthens, the importance of profitability factors for the ETFs' financial performance grows.
Keywords: 650; base point slack-based measure; ETFs; Europe; performance; US